2012
DOI: 10.1590/s1415-790x2012000200015
|View full text |Cite
|
Sign up to set email alerts
|

Tabagismo e consumo de álcool em estudantes universitários: prevalência e fatores associados

Abstract: The study aimed to estimate the prevalence of smoking and alcohol intake among university students from the Federal University of Pelotas, Brazil (UFPel), as well as to investigate factors associated with both habits. The sample included 485 students who were admitted to the university in 2008. Students were sampled randomly across all schools of the UFPel campus, and answered a pre-tested questionnaire, which was administered in the classroom by a member of the research team. Of the individuals interviewed, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1
80

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 19 publications
2
17
1
80
Order By: Relevance
“…20 A study comparing alcohol consumption between the sexes and the expectation of drinking of female university students in health area in Ribeirão Preto, revealed a high prevalence of binge drinking, regardless of the sex of the individual. 21 In this study, the prevalence of alcohol consumption by students at least once in their lifetime was 79.7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 A study comparing alcohol consumption between the sexes and the expectation of drinking of female university students in health area in Ribeirão Preto, revealed a high prevalence of binge drinking, regardless of the sex of the individual. 21 In this study, the prevalence of alcohol consumption by students at least once in their lifetime was 79.7%.…”
Section: Discussionmentioning
confidence: 99%
“…25 Research carried out among female university students from the south of the country found that more than 90% of those who consumed alcoholic beverages, started drinking before entering university. 20 This fact draws attention to the need to implement educational and preventive measures starting at high school in an attempt to reduce the problem of alcohol consumption at an early age. In the present study, 34.1% of the students reported abstinence from alcohol, while 65.9% had consumed alcoholic beverages within the previous year.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] No que se refere ao grau de escolaridade, a maioria dos entrevistados eram universitários, sendo que a literatura destaca os altos índices de consumo de bebidas alcoólicas em estudantes no ensino superior. [14][15][16] A maioria dos estudantes iniciam o consumo de bebidas alcoólicas antes da idade permitida por lei para a venda dessas substâncias, corroborando com a literatura. 17,18 Percebeu-se que a introdução à ingestão de álcool se deu principalmente em eventos sociais acompanhados por amigos e tendo como motivo principal a influência destes, seguido pela curiosidade, fato que pôde ser concluído por Chiapetti e Serbena, 19 Apesar das altas taxas de transgressão a Lei Seca identificadas, quase a totalidade dos estudantes relataram ter consciência dos problemas relacionados ao consumo de bebidas alcoólicas, principalmente no que se refere a sua associação com a direção corroborando com o estudo realizado por Campos e colaborados 20 e contrariando as recomendações realizados por Stamm e Bressam 17 que aventam a necessidade de desenvolver uma conscientização a respeito das consequências do álcool para prevenir seus efeito nocivos, já que percebeu-se que apesar da mesma existir nessa amostra, não coibi a combinação álcool e direção.…”
Section: Discussionunclassified
“…O aumento desse consumo nessa população tem gerado preocupações nos estudiosos da área e, em decorrência disto, estudos têm avaliado o padrão deste consumo, assim como intervenções preventivas efi cazes que o diminuam (Lorant et al, 2013;Pedrosa, Camacho, Lambert, & Oliveira, 2011;Ramis et al, 2012;Wagner et al, 2012).…”
Section: Segundo Dados Do I Levantamento Nacional Sobre O Uso De áLcounclassified
“…São mudanças no convívio social e nas atividades cotidianas que geram maior autonomia e liberdade ao estudante. No entanto, essa é uma fase que pode levar à aquisição de comportamentos pouco adequados e muitas vezes associados a um consumo excessivo de bebidas alcoólicas (Haas, Smith, Kagan, & Jacob, 2012;Lorant, Nicaise, Soto, & D´Hoore, 2013;Ramis et al, 2012). (Andrade, Duarte, & Oliveira, 2010) e de estudos como o de Grossbard et al (2010) e de Silva e Petroski (2012), essa fase tem sido considerada crítica, com maior vulnerabilidade para o início e manutenção do consumo de álcool.…”
unclassified